Improving resource allocation and incomes in Vietnamese agriculture: A case study of farming in the Dong Nai River Basin - Dewbre, Joshua (International Food Policy Research Institute, 2010)
This paper uses data collected in an extensive survey of farm costs in the Dong Nai River Basin of Vietnam to estimate the parameters of production functions for rice, vegetables, and coffee. These estimates are then combined with price information to estimate marginal value products for irrigation, fertilizer, labor, and other farm inputs. Comparing marginal value products of the various inputs across crops and with factor prices suggests there may be potential for improving resource allocation and farm incomes. One novel contribution is the consideration of water and irrigation—a concern of considerable interest amidst rising water scarcity in the region.